2020
DOI: 10.1016/j.psj.2019.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Using Guduchi (Tinospora cordifolia) as an eco-friendly feed supplement in human and poultry nutrition

Abstract: Guduchi ( Tinospora cordifolia ) is a well-recognized and widely distributed traditional plant that is used successfully in Indian Ayurveda medicine. T. cordifolia has shown many promising biological activities, such as antioxidative, antimicrobial, antihyperglycemic, anti-inflammatory, osteoprotective, hepatoprotective, antidiarrheal, and antistress effects. Guduchi is a rich source of protein and micronutrients, such as iron, zinc, copper, calcium, phosphorus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Adding oregano essential oil (300 and 600 mg per kg) in broiler chicken feed increases the ADG ( 92 ). Guduchi ( T. cordifolia ) has a positive effect on poultry growth performance, enhances the immune function in birds, and is used as a potent immunomodulator and an active antimicrobial agent in poultry ( 93 ).…”
Section: Antibiotic-free Management Strategies In Broilersmentioning
confidence: 99%
“…Adding oregano essential oil (300 and 600 mg per kg) in broiler chicken feed increases the ADG ( 92 ). Guduchi ( T. cordifolia ) has a positive effect on poultry growth performance, enhances the immune function in birds, and is used as a potent immunomodulator and an active antimicrobial agent in poultry ( 93 ).…”
Section: Antibiotic-free Management Strategies In Broilersmentioning
confidence: 99%
“…The Gujjar, Muslim and tribal people of District Jammu use this herb for bone pain [17]. The double effectiveness of giloy on neem tree has also been reported in the Bengal Pharmacopoeia of 18686 when people noticed the effectiveness of this plant as a tonic for its diuretic properties [18]. It is also used in the Unani system of medicine.…”
Section: Arthritismentioning
confidence: 89%
“…They added the histopathologic analysis of ascitic fluid showing a reduction in DLA cell count in tumor-bearing mice treated with AgNPs. Further, Kaler et al [ 45 ] reported that silver nanoparticles at very low concentrations showed very high activity on MCF-7 cells, showing almost 80% inhibitions. At higher concentrations (10–100 mg/mL) no significant difference in inhibition of cancer cells was observed with silver nanoparticles, and the IC50 value for the silver nanoparticles was less than 10 mg/mL.…”
Section: Discussionmentioning
confidence: 99%